Development of Law and Human Rights Awareness in Civics Education (Case Study of Law and Human Rights Awareness Students Forum (FPSH HAM) West Java) - Eka Nur’ala Hidayatin; Suwarma Al Muchtar (AIBPM Publisher, 2020)
At present learning about law and human rights is still centered in formal education in schools through learning Citizenship Education. But in reality learning law and human rights in Civics Education is not enough through formal education only, but the idea for developing legal awareness and human rights in Civics Education can also be implemented using other methods such as a forum called Law and Human Rights Awareness Student Forum (Forum Pelajar Sadar Hukum dan HAM (FPSH)) West Java that play the role as Citizenship Education. Several programs of law and human rights development activities carried out by FPSH West Java are following legal counseling for professional organization or communication, school socialization activities, training in introducing law to school, counseling legal awareness to schools, coordinating the exploration of legal awareness and human rights development programs, socialization of drug abuse prevention in the scope of family and school, village teaching, etc. This study aims to explore and analyze FPSH West Java programs in improving and developing student’s legal and human rights awareness in West Java so that it can overcome violations of law and human rights committed by students. The approach used in this research is qualitative with case study method. Data collection is obtained through documentation studies, observation techniques, interviews, participation, and discussion. Data analysis includes the submission of hypotheses, data interpretation, formulation of meaning, and data organization and categorization. The findings of this study indicate that FPSH West Java, in carrying out its program activities, is in accordance with its objectives and functions. FPSH West Java is able to create a program that collaborates with various parties and related institutions that aims to develop regional progress by involving students and college students. Even though FPSH HAM is still facing obstacles in the implementation of their programs but they strive to carry out good cooperation with various parties and related institutions in order to create a concordance and continuous founding.